1999
DOI: 10.1074/jbc.274.42.30222
|View full text |Cite
|
Sign up to set email alerts
|

The Mitogen-activated Protein (MAP) Kinase p38 and Its Upstream Activator MAP Kinase Kinase 6 Are Involved in the Activation of Signal Transducer and Activator of Transcription by Hyperosmolarity

Abstract: Environmental stress (e.g. aniso-osmolarity and UV light), hypoxia/reoxygenation, and reactive oxygen species activate intracellular signaling cascades such as the "stress-responsive" mitogen-activated protein kinases and nuclear factor B. We have recently shown that the Janus tyrosine kinase/signal transducer and activator of transcription (Jak/STAT) pathway is ligand-independently activated by hyperosmotic shock. In the present study, we show that besides STAT1 also the tyrosine phosphatase SHP2 became tyros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
63
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 36 publications
10
63
1
1
Order By: Relevance
“…Sorbitol (600 mM) was required for effective Stat activation, which was independent of gp130 or Jaks, but seemed to depend upon cell shrinkage (68,69). We did not detect Stat activation when 400 mM sorbitol was used, possibly secondary to low levels of Stat activation at this concentration, as previously reported (68,69).…”
Section: Figuresupporting
confidence: 57%
See 2 more Smart Citations
“…Sorbitol (600 mM) was required for effective Stat activation, which was independent of gp130 or Jaks, but seemed to depend upon cell shrinkage (68,69). We did not detect Stat activation when 400 mM sorbitol was used, possibly secondary to low levels of Stat activation at this concentration, as previously reported (68,69).…”
Section: Figuresupporting
confidence: 57%
“…When cells are treated with high concentrations of sorbitol, stress kinases can contribute to Stat activation (68,69). Sorbitol (600 mM) was required for effective Stat activation, which was independent of gp130 or Jaks, but seemed to depend upon cell shrinkage (68,69).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…27 Although most reports link MAPKs to nuclear signaling, it seems clear that all of them phosphorylate both nuclear and cytoplasmic targets. The JNKs and p38s are activated by most environmental stresses (hence the name SAPKs for Stress Activated Protein Kinases) such as hyperosmolarity 28,29 and some of them can also be activated by cytokines and TNF-a. 9,26 ± 30 All these kinases play critical roles as components of the signal transduction pathways that control cell differentiation, the cell cycle, and cell death.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to tyrosine phosphorylation, the serine phosphorylation of Stat molecules is also necessary for the maximal activation of transcription (13,14). Several lines of evidence suggest the role of different Ser/Thr kinases in serine phosphorylation of Stat molecules and their transactivation (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Our recent studies demonstrated that p38 MAPK regulates serine 727 phosphorylation on Stat1 and Stat3 and that p38 MAPK activity is required for IL-13-induced 15-LO expression (27).…”
mentioning
confidence: 99%